CYTOKINE PROFILE IN PROGRESSIVE HYPERGLYCEMIA: TNF-Α, IL-6 AND IL-10 IN THE EXPERIMENT (E Global Congress, 2025)
Diabetes mellitus and its primary characteristic, hyperglycemia, cause metabolic disturbances accompanied by intensified inflammatory processes. Levels of pro-inflammatory cytokines such as TNF-α and IL-6 increase, while anti-inflammatory cytokines like IL-10 decrease. This imbalance may exacerbate the complications of the disease.